PERSAMAAN HUKUM KEBEBASAN BERPOLITIK ANGGOTA TENTARA NASIONAL INDONESIA DAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM PEMILIHAN UMUM DI INDONESIA - Basuki Kurniawan (JURNAL AKTA YUDISIA, 2021)
ABSTRACT  The members of INA and PIR don’t give right to vote and be elected in general elections because there is worried about right to vote and be elected will be bringing on not neutral in general election, with the result that general elections principle is direct, general, secret, honest, and fair will not be achieved if right to vote and be elected is given. Although that worried still be able to debate in theoretical. It is becaused if right to vote and be elected for members of INA and PIR are given, so will not influence the vote result majority in general elections. The concept  to give right to vote and be elected  for members INA and PIR in general elections need to be implemented, because in the first general elections in 1955 the members of INA and PIR follow to vote and be elected in general election, and than there was not problem happen in thats time. Because of that  be alternative thought bargained  in this thesis; The concept  of  legal protection  for members INA and PIR in political freedom is looked from human right protection principle is given  freedom for members INA and PIR  to vote the candidates house representatives, house representative region, house representative people, President and Vice President with free without any pressures from the institution INA and PIR. And than  for the members INA and PIR propose their self as candidates the members House Representative, House Representative Region, House Representative People, President and Vice President permitted to be candidate as form of political freedom to every people Keyword: legal equality, political freedom, general election.